Penerapan Dashboard Business Intelligence untuk Analisis Piutang Customer pada Perusahaan Manufaktur - Bintang Noviansyah Syamsu; Dedi Trisnawarman; Agus Budiyantara (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
Manual management of customer receivables in manufacturing companies often leads to inefficiencies, including slow analysis processes, difficulty in monitoring outstanding balances, and limited ability to track payment trends comprehensively. This study designed a Business Intelligence Dashboard using Microsoft Power BI to address these issues at PT. XX Industry, employing a Software Development Life Cycle (SDLC) approach consisting of four stages: Planning, Analysis, Design, and Implementation. During the design phase, a data warehouse was built using a star schema model in SQL Server Management Studio, followed by an Extract, Transform, Load (ETL) process to ensure data accuracy and consistency prior to integration into Power BI. Five Key Performance Indicators (KPIs) were established collaboratively with company management through a series of online discussions, comprising Total Invoice, Total Payment, Total Receivables, Payment Rate, and Average Payment Time, all implemented using DAX expressions. The resulting dashboard features monthly trend visualizations, customer-based receivables distribution, and interactive filter capabilities. System testing confirmed that all components functioned correctly, while ETL validation verified consistency between processed and source data. User Acceptance Testing (UAT) conducted by management yielded an average score of 4.7 out of 5, reflecting a very high level of user acceptance. Overall, this dashboard proved effective in improving receivables monitoring efficiency and supporting faster, data-driven decision-making.